Carbon capture and water quality of the Río de Oro biocorridor, Ecuador (Agroindustria, Sociedad y Ambiente, 2025)
In the canton of Portoviejo, Ecuador, the Río de Oro Biocorridor project was developed with the goal of restoring the Río de Oro canal and its surroundings and mitigating current environmental pollution. This project requires monitoring and follow-up through activities such as biodiversity measurement, tree structure and function, and carbon storage, among others, to assess its scope and goals achieved. In this regard, the goal was to evaluate the carbon content of the aboveground biomass and the water quality of the Río de Oro Biocorridor in Ecuador to understand the project's impact on the area and determine whether the initial objectives were met. Tree species were identified, and dasometric variables and the carbon sequestered by aboveground biomass were determined. Water quality was also assessed in the initial, middle, and final zones of the canal. One hundred and two individuals were identified among the trees of the Río de Oro Biocorridor, distributed among 17 species, with a predominance of Bauhinia aculeata and Handroanthus bilbergii. The largest contribution to carbon sequestration comes from the species Samanea saman and Bucida buceras, with the increase in captured carbon and CO2 observed to increase with increasing aboveground biomass. Additionally, it was observed that most of the canal water parameters analyzed met the limits of Ministerial Agreement 097-A. The development of the Río de Oro biocorridor project has allowed for the recovery of a useful public space for improving the quality of life of its inhabitants through various ecosystem benefits. This demonstrates the fulfillment of the project's objectives and makes it a management model to follow for solving various problems facing cities, including climate change.
Keywords: captured carbon, quality, urban forests, forest inventory, Río de Oro biocorridor.